A high-order finite element continuation for buckling analysis of porous FGM plates. (15th March 2023) - Chaabani, Hamza; Mesmoudi, Said; Boutahar, Lhoucine; Bikri, Khalid El
Abstract: This work presents an effective approach to investigating the buckling and post-buckling behavior of porous FGM plates. The main objective of the present analysis is to use a High Order Continuation based on the Asymptotic Numerical Method with the Finite Element Method for nonlinear behaviors of a Porous Functionally Graded Material plate (PFGM) with different porosity distributions under various types of transverse loads. In our study, we will take into account the lack of uniform and non-uniform porosity using a Higher-order Shear Deformation Theory (HSDT). The adapted solver proves to be more effective for analyzing non-linear mechanical phenomena and more precisely the post-buckling analysis of the PFGM plates. Indeed, this numerical high order algorithm presents an adaptive step length to the local nonlinearity of the solution branch and to detect easily the bifurcation points and bifurcated branches. When compared to iterative techniques like Newton–Raphson, the proposed high-order algorithm has the benefit of speeding up the resolution of nonlinear problems. The mathematical formulation is based on the higher-order shear deformation plate theory taking into consideration geometrical nonlinearity and initial imperfections. Numerical results of a parametric study on the effect of various types of load, porosity distribution, grading index, porosity index and different span-to-thickness ratios will be investigated. Highlights: A High Order Continuation is applied to solve nonlinear buckling of porous FG plates. Effects of various types of loads, porosity distribution, grading index, porosity index and different span-to-thickness on the critical buckling loads of a porous FG plates were examined. A finite element model is used in the framework of Higher Order Shear Deformation Theory.